Meningkatkan Kesadaran Masyarakat Desa Jompie Terhadap Lingkungan Yang Sehat Dan Asri Melalui Gaul (Gerakan Aksi Untuk Lingkungan) - Irwan, Irwan; Ja'faruddin, Ja'faruddin; Faisal, Ahmad; Pratiwi, Annisa Triananda; Wahyuni, Maya Sari (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
KKNT Mathematics Department, Makassar State University in Jompie village, Ulaweng subdistrict, Bone district is a form of community service activity. The problem still faced by the people of Jompie Village is that they have not created a healthy and beautiful environment. Therefore, KKNT students held a work program GAUL to overcome this problem by carrying out community service activities to clean the environment so that a healthy and clean environment is obtained. The results obtained during the implementation of the work program GAUL were the construction of rubbish bins at several points, painting village boundaries, carrying out community service, and making gates.